(untitled) - Damjanov, Ivan (Philadelphia, 2009)
This completely new textbook takes an integrative, problem-based approach to pathophysiology, creating an effective bridge from basic science to clinical practice. Preeminent pathology practitioner, author, and instructor Ivan Damjanov, MD, PhD skillfully provides you with the rich understanding of disease mechanisms you need to succeed on the USMLE and beyond. Clinical vignettes in each chapter, presented in a problem-based format, demonstrate the practical relevance of pathophysiology principles, and hundreds of full-color diagrams clarify even the most difficult concepts. Plus, full-text online access via Student Consult further enhances learning and study. The result is a comprehensive yet succinct source that is ideal for today's medical students.
Keywords: Physiology, pathological,Pathology, clinical; Methods